Accident Prevention Block to Move an Automobile From Traffic Collision - Rajiv, Charles Samuel (European Publisher, 2019)
Traffic accidents are one of the main reasons for the loss of lives around the world. To prevent traffic accidents and protect lives, many systems are being tried and implemented. A tired/sleepy automobile driver puts his life and other lives at risk, which may become fatal. An effective solution needs to be implemented to help the driver in the event of losing consciousness and move the vehicle to safety, to avoid any collision with traffic. This proposed solution is fueled by recent technological advancements like IoT (Internet of Things) and Machine Learning. In the present work, an attempt has been made to propose an accident prevention block in automobiles that can sense the tired/sleepy driver via a camera and algorithms, to maneuver the vehicle to safety. The camera is fixed on the steering wheel that is linked to the block. The automobile is controlled by APB in case of an emergency situation by interacting with the ECU, which in turn controls automobile speed and robotically brings it to the side of the road with the help of sensors. When the data inputs pertaining to the driver are received, the data from other sensors are retrieved and a decision could be arrived to ascertain whether the vehicle is in danger or could be a potential danger for other lives as well as the life of the driver. The development of an Accident Prevention Block (APB) is an effort to safeguard vehicles from accidents and save precious lives.